LOGISTIK PERLAWANAN: AGENSI MASYARAKAT LOKAL DALAM ORGANISASI DAPUR UMUM DI PARIT VII TUNGKAL I, JAMBI, 1945–1949 - Tatik Winarti, Putri Ranjani; Mursal, Irhas Fansuri; Rahman, Abd (Jurnal Ceteris Paribus, 2026)
This study examines the strategic role of the Public Kitchen (Dapur Umum) organization as a multi-functional defense node within the context of the Dutch Military Aggression II (1945–1949) at Parit VII Tungkal I, Tanjung Jabung Barat Regency, Jambi. Unlike studies of revolutionary logistics centered in Java, this research foregrounds the agency of a coastal-swamp rural community long marginalized in national historical narratives. Employing a four-stage historical method—heuristics, source criticism, interpretation, and historiography—alongside a social history approach, this study examines how local society organized a subsistence strategy under conditions of asymmetric warfare. The principal finding is that the Public Kitchen at Parit VII Tungkal I functioned not merely as a food logistics provider but also as an arms storage facility, an emergency field hospital, and a guerrilla defense coordination hub. Its resilience against Dutch intelligence was sustained by three structural factors: the geographical advantage of the narrow Parit Gantung waterway, the kinship solidarity of the Banjar-Malay community, and the charismatic leadership of H. Mangun. These findings reinforce a history-from-below perspective in the historiography of the Indonesian Revolution, demonstrating that rural community agency constituted a structural—not merely supplementary—component of the independence struggle.